Clinical and Surgical Consequences of COVID-19 Pandemic for Patients with Urological Problems - Rashid, Md Mamunur; Rahman, Md Mostafizur; Arafuzzaman, KH; Alam, Mahmud; Islam, Md Merajul (Bangladesh Journal of Urology, 2022)
Objective: To discuss the impact of COVID-19 on Urological practice and their management and to review some of the available recommendations reported in the literature. Materials and Methods: In the current review the PubMed database was searched to identify all the related reports discussing the impact of COVID-19 on urological field and how the urological issues and cases can be managed is discussed. Results: The COVID-19 pandemic is the latest and biggest global health threat. Medical and surgical practices have changed dramatically to cope with the current challenge. This changes include postponements of most of the elective out patient’s visits and urological procedures to save facilities and resources for urgent cases and patients with COVID-19. Conclusion: Over the coming months, healthcare workers including urologists will be facing increasingly difficult challenges and consequently they should adopt triage strategy to avoid wasting of medical resources and they should endorse sufficient protection procedures to guard against infection when dealing with COVID-19 patients. Bangladesh J. Urol. 2021; 24(1): 33-36